Geometry of flocks and n-ary groups - Dog, S. (Algebra and Discrete Mathematics, 2019)
Semiabelinan flocks and n-ary groups are characterized by the properties of parallelograms and vectors of the affine geometry defined by these flocks and n-ary groups.